Psychometric evaluation of Malay version of Peritraumatic Distress Inventory (M-PDI) and Peritraumatic Dissociative experiences Questionnaire (M-PDEQ) using the sample of flood victims in Kuching, Sarawak, Malaysia - Ferlis Bullare @ Bahari; Mohd Dahlan A. Malek; Adeymend Reny Japil; Lailawati Madlan Endalan; Jasmine Adela Mutang; Rosnah Ismail; Fattin Abdul Ghani (Nauka Publishers, 2017)
The main purpose of the current research is to investigate the psychometric characteristics of Malay version of Peritraumatic Distress Inventory (M-PDI) and the Peritraumatic Dissociative Experiences Questionnaire (M-PDEQ). The original scales of PDI and PDEQ are used to measure the traumatic stress experienced by individuals during and immediately after and within or during a few minutes or hours of the traumatic event happened. Both instruments have been employed in past studies in assessing the traumatic experiences of individuals affected by disaster or terrorist attacks. Psychometric evaluation involved convergent and discriminant validity was conducted using SmartPLS 2.0. Whereas, internal consistency and correlation analysis were tested using the IBM Statistical Package for Social Sciences (SPSS) Version 23.0. A total of 116 flood victims from several areas in the district of Kucing and Kecil Siburan, Sarawak, Malaysia were involved in this study. These two areas were affected by the flood at the end of 2014 until early 2015. The findings showed that both M-PDI and M-PDEQ demonstrated a sufficient convergent and discriminant validity. The level of internal consistency for M-PDI ( a = 768) and M-PDEQ ( a = 918) was at an acceptable level. In addition there was a significant positive correlation between M-PDI and M-PDEQ. Both M-PDI and M-PDEQ have been proven as a valid instrument to be used in the contexts of flood victims in Malaysia, particularly in the Kucing District of Sarawak.